Features of the formation of the fish helminth fauna in the lower reaches of the Hrazdan River (Armenia) under anthropogenic pressure - Hovhannisyan R.L.; Rukhkyan M.Ya.; Gabrielyan B.K. (Трансформация экосистем)
Data from studies of the species composition of the fish helminth fauna and the degree of fish infection in the lower reaches of the Hrazdan River are presented. The studies were conducted in 2019–2020; 454 individuals of 15 fish species were examined. The detected helminth fauna was characterized by low species diversity, as a result, 5 species of helminths were identified: 1 species of Monogenea, 1 species of Trematoda, 2 species of Cestoda and 1 species of Nematoda. The total infection of fish by helminths was 34.1%. The detected helminths were localized mainly in the body cavity, intestine, eye lenses and on the gills of fish. The largest number of helminth species was noted in khramicarps and crucian carps. In almost all the studied areas of the lower reaches of the river, the most common of the detected species of helminths were plerocercoids of the cestode Ligula intestinalis (L., 1758) and metacercariae of the trematode Diplostomum sp. Nordmann, 1832.